konsep kerja dan produksi menurut ibnu khaldun dalam perspektif ekonomi modern: The Concept of Work and Production According to Ibn Khaldun in a Modern Economic Perspective - cahyana prayoga cahyana; Linamarlina susana (Khulasah : Islamic Studies Journal, 2026)
Classical Islamic economic thought plays a crucial role in shaping the conceptual foundation of modern Islamic economics, particularly through Ibn Khaldun's work, Al-Muqaddimah. This study aims to analyze Ibn Khaldun's concepts of work and production and examine their relevance in the context of modern Islamic economics. The research method employed is a literature review, examining Ibn Khaldun's primary works, Islamic economics books, and relevant scientific journal articles. The data obtained were analyzed descriptively and qualitatively to systematically and comprehensively understand Ibn Khaldun's views. The results show that Ibn Khaldun views work as the primary source of economic value, generating added value and becoming a crucial factor in creating social prosperity. Furthermore, production is understood as the result of the division of labor and specialization, which encourages increased efficiency and productivity. This concept aligns with the principles of modern Islamic economics, particularly in human resource development, productivity enhancement, and the achievement of equitable and sustainable social welfare.